The Endogamous Marriage in the Population of Doukkala (Morocco) - Khair, Abderrazak El; Dahbi, Noura; Cheffi, Khadijah; Talbi, Jalal; Hilali, Abderraouf; Ossmani, Hicham El (International Journal Labs, 2023)
Background: Endogamy is an ancient matrimonial practice deeply rooted in the population culture. It involves choosing a spouse from the same group who shares common conditions. This type of alliance is dictated by socio-cultural, socio-economic and geographical conditions. Aim: This paper examines endogamous marriage among the Moroccan population of Doukkala. Method: A survey was conducted among 1361 couples from the Doukkala region. Geographical endogamy in this population was determined by using a questionnaire that collected data on the place of birth, the place of residence before and after the marriage of the couples studied. Findings: The endogamy in the Moroccan population of Doukkala reaches 84.79%. The level of this marital behavior in rural areas is 87.34% compared to 60.57% registered in urban areas. The intergenerational evolution of endogamy reaches high levels in the first (92.84%) and second (91.02%) generations compared to the last generation (58.56%).